The Inquiry-based teaching instruction (IbTI) in Indonesian secondary education: What makes science teachers successful enact the curriculum? - Effendı-Hasıbuan, Muhammad Haris; Harızon; Ngatıjo; Mukmının, Amirul (Journal of Turkish Science Education, 2024)
The inquiry-based teaching instruction (IbTI) has been practiced internationally to improve student competency in science. The implementation of this strategy has been recommended by the science curriculum in Indonesia since 2003. However, it is not still implemented successfully in schools. The implementation is likely unsuccessful to achieve its goals and this has been demonstrated by the results of an international assessment program called PISA in which the ranks of Indonesia have not increased since 2003. This study; thus, focused on this issue by assessing the implementation of IbTI in secondary schools in Jambi City, Indonesia. In addition, this study included constraints that interfered with the implementation. A researcher-designed questionnaire was sent out to 107 science teachers in Jambi city and 70 (65.4%) teachers returned the questionnaires. The results showed that most of the participants did not use IbTI in their science classrooms. They predominantly used the more traditional teaching strategies such as lecturing despite of the fact that the use of IbTI had been recommended by the curriculum. Four major perceived-constraints including the unsupportive educational settings and insufficient facilities and knowledge had been identified interfered with the implementation. These findings may provide a logical explanation to the low science scores of the Indonesian students as showed by PISA. This study thus highlighted the need of providing the science teachers with reasonable supports for replacing their traditional-type instructions with more student-centered ones such as IbTI. The findings of this study are also beneficial for those in other developing countries who are endeavoring to implement inquiry due to the similarity in their educational context.
Keywords: curriculum; inquiry-based teaching instruction; science teachers